Critical Enablers that Mitigate Supply Chain Disruption: A Perspective from Indian MSMEs. (February 2023) - Bhattacharya, Lipika; Chatterjee, Ayan; Chatterjee, Debmallya
The study attempts to identify the critical enablers that can mitigate supply chain (SC) disruption and model the interconnectedness among them in the context of the Indian Micro, Small and Medium Enterprises (MSMEs). The supply chain in many Indian MSMEs has been seriously affected by the COVID-19 pandemic, bringing forth the need to identify avenues that can mitigate the disruptions. This study conducts a two-stage qualitative interview and a structured interview with MSME owners. Domain experts are associated with the automotive, aerospace and design services industries. Based on their responses, we have identified seven major critical enablers specific in the context of Indian MSMEs. To model the interconnection among these factors, we have used the ISM (Interpretive Structural Modelling) approach. Results suggest that 'top management support' is the most crucial enabler in the hierarchy. Further, we find that if the supply chain is designed efficiently with redundancy in mind and the culture of the MSME remains conducive, advanced forms of 'multi-sourcing' and differentiated logistics can be explored to mitigate supply chain disruption.